Feasibility study of functionalized graphene for compatibility with cement hydrates and reinforcement steel - Sideri, Sofia (My University, 2014)
Cement-based concrete is a widely used material for a great variety of constructions. Although, cement has great properties and high performance, its intrinsic brittleness is a weakness that requires further investigation for improvement. Graphene demonstrates a number of excellent properties, such as high flexibility, 1 TPa Young’s modulus, 130 GPa tensile strength, high electrical and thermal conductivity. This study investigated the feasibility of implementing graphene into the cement matrix for improving its compressive and tensile or flexural strength. In addition, graphene coating was also investigated for protecting reinforcement steel bars in concrete from corrosion. Within the framework of this study, three main tests were conducted: compressive tests and tensile test on specimens of cement paste and mortar containing graphene, and half-cell potential test on corrosion initiation of steel bars coated with graphene and embbeded in cement mortar. From the literature, several research studies indicate the significance to investigate the graphene and its derivatives with cement composites within a multi-scale approach. According to one of the studies addition of graphene oxides (GO) with 1.5% by weight of cement revealed an increase in tensile strength by 48% compared with the cement mixture without graphene oxides. The Field Emission Scanning Electron Microscopy (FE-SEM) images showed good bonding between GO and the cement particles. The results obtained from the experimental study of this master thesis work did not, however, reflect graphene’s potential due to the fact that the functionalized graphene used in this study contained functional groups with silicon oxides, which were polymerized and inactive for chemical interaction with the cement hydrates. The study results from the literature also proved that single but also multi-layer graphene can work as anti-corrosion coating. The corrosion test from this master thesis work indicated that the specimens with graphene coating revealed a delayed corrosion initiation and some repassivation-depassivation cycles, as a result of the higher amount of chlorides needed for the depassivation of the passive film.
Keywords: Building Futures; Byggnadsteknik; Building Futures; Building engineering